A new gel material suitable for reservoir profile control, its preparation method and application
Patent Information
- Application Number
- CN202610735186.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-26
- Publication Date
- 2026-09-29
AI Technical Summary
然而,常规的聚丙烯酰胺类水凝胶在高温高盐环境下存在明显的缺陷:高温会加速酰胺基团水解,破坏凝胶的三维网络结构;高浓度的盐离子则会压缩凝胶双电层,导致凝胶脆化、机械强度大幅下降,最终导致封堵有效期大幅缩短,无法满足高温高盐油藏的长期开发需求
[0024]1.本发明通过分子结构设计,引入含咪唑环的1-乙烯基咪唑功能单体,显著提升了凝胶的热稳定性,可抑制高温下的聚合物链段松弛与网络解体,使得凝胶在120℃的高温环境下仍能保持结构完整,不会发生水解破坏,解决了现有凝胶仅能耐受80℃以下中低温的技术缺陷,可适配深部高温油藏的作业需求。
Smart Images

Figure CN122832189A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer gel materials technology, and more specifically, to a novel gel material suitable for reservoir profile control, its preparation method, and its application. Background Technology
[0002] Water channeling and water plugging are core technologies for improving oil recovery during oilfield development. By injecting plugging materials into the formation, the water absorption profile of the reservoir is adjusted, and high-permeability water channeling channels are blocked, thereby effectively inhibiting water channeling and improving water drive development efficiency. It is a key technical means for stabilizing and increasing production in old oilfields.
[0003] As conventional low-temperature and low-salinity reservoirs gradually enter the middle and late stages of development, the development of high-temperature and high-salinity reservoirs has become an important direction for increasing oilfield production. These reservoirs typically have formation temperatures exceeding 120℃ and formation water salinity reaching 20×10⁻⁶. 4 The concentration of mg / L far exceeds the environmental conditions of conventional oil reservoirs, placing extremely stringent requirements on the temperature and salt resistance and long-term stability of profile control and water shut-off materials.
[0004] In existing technologies, polyacrylamide hydrogels are the most widely used materials in oilfield profile control and water shut-off operations. These materials possess good thickening and sealing properties, and perform well in conventional reservoirs. However, conventional polyacrylamide hydrogels have significant drawbacks in high-temperature and high-salt environments: high temperatures accelerate the hydrolysis of amide groups, disrupting the gel's three-dimensional network structure; high concentrations of salt ions compress the gel's electric double layer, leading to gel embrittlement, a significant decrease in mechanical strength, and ultimately a drastically shortened sealing period, failing to meet the long-term development requirements of high-temperature and high-salt reservoirs.
[0005] Therefore, there is an urgent need for a profile control and water shut-off material that can maintain structural stability in extreme high-temperature and high-salinity environments, while possessing excellent mechanical strength and long-term sealing performance, in order to support the efficient development of high-temperature and high-salinity oil reservoirs. Summary of the Invention
[0006] In view of this, the present invention provides a novel gel material suitable for reservoir profile control, its preparation method, and its application. This gel material can withstand high temperatures of 120°C and 20×10⁻⁶ ℃. 4 It can maintain structural stability and show no hydrolysis even in harsh reservoir environments with high salinity of mg / L. At the same time, it has excellent mechanical strength and plugging performance. It solves the technical problems of existing polyacrylamide gels being prone to hydrolysis, embrittlement and short plugging period in high temperature and high salinity reservoirs. It can meet the needs of profile control and water shut-off operations in high temperature and high salinity reservoirs.
[0007] The technical solution of this invention is as follows:
[0008] In a first aspect, the present invention provides a novel gel material suitable for reservoir profile control, wherein the gel material is formed by pre-crosslinking and hybridization reaction of 16%-17% polymer monomer mixture, 0.6%-1% crosslinking agent mixture, 0.2%-0.81% surfactant, 0.02%-0.03% initiator and the balance deionized water by weight percentage;
[0009] The polymer monomer mixture includes acrylamide and 1-vinylimidazole; the crosslinking agent mixture includes divinylbenzene and vinyltrimethoxysilane; the surfactant is sodium dodecyl sulfate; and the initiator is potassium persulfate.
[0010] Further, the mass ratio of the acrylamide to the 1-vinylimidazole is (2-4):(0.07-0.2).
[0011] Further, the mass ratio of the divinylbenzene to the vinyltrimethoxysilane is (0.05-0.13):(0.05-0.07).
[0012] Furthermore, the gel material is subjected to a temperature of 120°C and a temperature of 20 × 10⁻⁶. 4 The swelling rate after aging in mg / L saline for 7 days was 388%-659%.
[0013] Furthermore, the tensile strength of the gel material is not less than 13 kPa.
[0014] Secondly, based on the same inventive concept, the present invention provides a method for preparing a novel gel material suitable for reservoir profile control as described in any one of the first aspects, comprising the following steps:
[0015] Acrylamide and sodium dodecyl sulfate were added to deionized water and stirred until completely dissolved to obtain the first mixture.
[0016] 1-Vinylimidazole, vinyltrimethoxysilane and divinylbenzene were added sequentially to the first mixture and stirred until homogeneous to obtain the second mixture.
[0017] Add potassium persulfate aqueous solution to the second mixture, stir and mix to obtain the reaction precursor solution;
[0018] The reaction precursor solution was transferred to a sealed container, nitrogen gas was introduced to purge oxygen, and the container was sealed. The reaction was carried out at 50℃-70℃ for 9-12 hours to obtain the gel material.
[0019] Furthermore, the concentration of the potassium persulfate aqueous solution is 0.02 g / mL to 0.04 g / mL.
[0020] Furthermore, the stirring speed is 300rpm-500rpm, and the stirring time is 15min-45min.
[0021] Furthermore, the nitrogen purging time is 30-60 minutes.
[0022] Thirdly, based on the same inventive concept, this invention provides a novel gel material suitable for reservoir profile control as described in the first aspect, or a novel gel material suitable for reservoir profile control prepared by the preparation method described in the second aspect, with a formation temperature ≥120℃ and formation water salinity ≥20×10⁻⁶. 4 Application of mg / L in reservoir profile control and water shut-off operations.
[0023] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:
[0024] 1. This invention introduces a 1-vinylimidazole functional monomer containing an imidazole ring through molecular structure design, which significantly improves the thermal stability of the gel. It can inhibit polymer chain relaxation and network disintegration at high temperatures, so that the gel can still maintain structural integrity at a high temperature of 120°C without hydrolysis damage. This solves the technical defect of existing gels that can only withstand medium and low temperatures below 80°C, and can be adapted to the operational needs of deep high-temperature oil reservoirs.
[0025] 2. This invention constructs a high-density, stable three-dimensional crosslinked network by introducing the rigid crosslinking agent divinylbenzene and the hybrid coupling agent vinyltrimethoxysilane. Simultaneously, it utilizes the dynamic coordination of the imidazole ring with metal ions to overcome the limitations of traditional gels when exposed to high concentrations of Ca. 2+ Mg 2+ The problems of plasma embrittlement and hardening make the gel brittle at 20×10⁻⁶. 4 It can maintain stable swelling properties even in an ultra-high mineralization environment of mg / L, and its structure will not be destroyed by the action of salt ions, thus solving the technical problem of poor salt resistance of existing gels.
[0026] 3. The gel material prepared by this invention has excellent mechanical strength, with a fracture strength of up to 31 kPa, which is much higher than the strength level of existing soft gels. It can withstand the shear force and formation pressure during oilfield injection, avoiding the problem of insufficient strength of existing gels and easy erosion by formation fluids, thus ensuring the long-term effectiveness of the sealing.
[0027] 4. The gel material of the present invention has excellent plugging performance, with a plugging rate of over 90%, which is much higher than the 69.5% of the existing ordinary polyacrylamide gel. It can effectively block high-permeability channels, realize fluid flow diversion, significantly increase the swept volume of water injection displacement, and effectively improve the oil recovery rate.
[0028] 5. The preparation method of the present invention is simple, the raw materials are readily available, the reaction conditions are mild, and no complex equipment or harsh reaction conditions are required. It is suitable for large-scale industrial production and field application. At the same time, the raw materials are green and environmentally friendly, do not harm the formation, and have good prospects for field application. Attached Figure Description
[0029] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 This is a schematic diagram of the molecular network structure of the hydrogel of the present invention;
[0031] Figure 2 This is a schematic diagram illustrating the synthesis mechanism of the gel system of the present invention;
[0032] Figure 3 This is a sample image of the gel material prepared in Example 3 of the present invention;
[0033] Figure 4 This is a SEM side view of the gel material sample prepared in Example 3 of the present invention;
[0034] Figure 5 The images show the infrared test results of the gel material samples obtained in Examples 1-4 of this invention.
[0035] Figure 6 Thermogravimetric analysis results of the gel material samples prepared in Examples 1-2 of this invention are shown in the figure.
[0036] Figure 7 These are frequency scan diagrams of the product samples from Examples 1-4 and Comparative Example 1 of the present invention;
[0037] Figure 8 The samples from Examples 3 (left) and 4 (right) of this invention were aged for 7 days (120°C, 20×10⁻⁶ ℃). 4 (mg / L) effect diagram;
[0038] Figure 9 This is a schematic diagram of profile control and water shut-off in heterogeneous reservoirs according to the present invention. Detailed Implementation
[0039] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0040] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0041] To address the problems existing in the prior art, according to one aspect of the present disclosure, a novel gel material suitable for reservoir profile control is provided, which is formed by pre-crosslinking and hybridization reaction by weight percentage of 16%-17% polymer monomer mixture, 0.6%-1% crosslinking agent mixture, 0.2%-0.81% surfactant, 0.02%-0.03% initiator and the balance deionized water;
[0042] The polymer monomer mixture includes acrylamide and 1-vinylimidazole; the crosslinking agent mixture includes divinylbenzene and vinyltrimethoxysilane; the surfactant is sodium dodecyl sulfate; and the initiator is potassium persulfate.
[0043] It should be noted that the acrylamide (Am) of this invention is a monomer containing polymerizable vinyl groups (CH2=CH-) and hydrophilic amide groups (-CONH2). After polymerization, a large number of acrylamide units connect to form long polyacrylamide chains, constituting the hydrophilic three-dimensional network framework of the hydrogel, which can absorb and lock in a large amount of water. The vinyl groups on the long chains can serve as "anchors" for chemical modification. Through free radical copolymerization with functional monomers and crosslinking agents, specific structural units or crosslinking nodes with temperature resistance, salt resistance, and reinforcing effects can be chemically bonded to the polymer backbone, thereby achieving directional design of the basic gel network properties.
[0044] 1-Vinylimidazole (VIM) is an organic compound containing polymerizable vinyl groups and an imidazole ring that provides rigidity and stability. It can serve as a monomer to enhance the rigidity and thermal stability of polymer chains, inhibiting chain relaxation and network disintegration at high temperatures, thus maintaining the structural integrity and elasticity of gels at high temperatures. Furthermore, it can form high-strength, reversible metal-coordinate bonds with metal ions in formation water. These dynamic bonds dissipate energy and are not easily affected by high concentrations of monovalent salts, thereby overcoming the limitations of traditional gels where carboxylic acid groups react with Ca2+. 2+ / Mg 2+The embrittlement caused by precipitation can endow the gel with excellent mechanical strength and salt resistance. Therefore, this invention chooses to graft it onto long chains of polyacrylamide to enhance the temperature resistance and strength of the gel.
[0045] Divinylbenzene (DVB) is a crosslinking agent with two polymerizable vinyl groups, whose key role is to construct a high-density, rigid three-dimensional crosslinked structure in the hydrogel network. The molecular structure of DVB comprises a benzene ring and two vinyl groups. The benzene ring structure enhances the thermal stability of the network, while its high crosslinking density constructs a robust three-dimensional framework that resists formation fluid erosion, providing the gel with the essential structural strength and dimensional stability necessary for high-temperature and high-salt environments. Therefore, this invention selects it as the primary crosslinking agent to obtain a more stable gel structure.
[0046] Vinyltrimethoxysilane (VTMS) is a coupling agent containing polymerizable vinyl groups and hydrolyzable siloxanes, which can significantly improve the structural integrity, temperature resistance, and interfacial stability of gels at the molecular level. The siloxane (Si-O-Si) inorganic network formed by the hydrolysis and condensation of VTMS has low surface energy and high hydrophobicity. After interpenetration with the organic network, this network forms a dense physical barrier within the gel, significantly hindering the penetration and diffusion of high-concentration salt water ions. At high temperatures (>120°C), the siloxane network formed by VTMS can act as a reinforcing framework, and its coefficient of thermal expansion is much lower than that of organic polymers, effectively suppressing the overall thermal expansion and softening of the gel, thus resulting in a higher heat distortion temperature. Therefore, this invention selects it as the second crosslinking agent, working synergistically with DVB in the gel structure to make the gel structure more robust and suitable for high-temperature, high-salt reservoirs.
[0047] Sodium dodecyl sulfate (SDS) is a highly efficient surfactant. Its amphiphilic molecular structure significantly reduces the interfacial tension between oil and water. Its hydrophobic long chains can uniformly disperse and stabilize incompatible hydrophobic monomers or functional components (VIM, DVB, VTMS) in the reaction solution, thereby ensuring the formation of a chemically homogeneous and stable gel network. Simultaneously, SDS optimizes the network's topology and microscopic homogeneity by regulating the microenvironment of the polymerization reaction, ensuring excellent stability and repeatability of the material's properties, enabling it to withstand the extreme conditions of high-temperature and high-salinity oil reservoirs.
[0048] Potassium persulfate (KPS) is a thermally decomposable, water-soluble initiator. Under thermal conditions of 60°C, it decomposes to generate primary free radicals, which efficiently initiate the copolymerization of monomers such as acrylamide and 1-vinylimidazole, as well as divinylbenzene and vinyltrimethoxysilane. KPS combines reaction efficiency, process safety, and low cost, making it a suitable initiator for novel sealing materials.
[0049] Deionized water is used as the sole reaction medium and solvent to completely eliminate the uncontrollable interference of common metal ions and impurities on polymerization kinetics, network structure formation, and the performance of the final product. A pure reaction environment ensures that functional monomers and crosslinking agents react precisely according to the pre-set mechanism, which is a crucial prerequisite for achieving a uniform gel network structure, stable and reproducible performance, and ensuring that its temperature and salt resistance properties are entirely derived from intrinsic chemical design.
[0050] Please refer to Figure 1 The reaction mechanism of this invention is as follows: ① Free radical polymerization (organic network formation): The vinyl groups of acrylamide, VIM, VTMS and DVB open their double bonds under the action of free radical initiators; acrylamide forms the main CC backbone as the polymer skeleton; the two vinyl groups of DVB participate in different chain segments and form crosslinking points; the vinyl groups of VTMS connect the main chain, and the siloxane side groups hang on the main chain; VIM, as a functional monomer, is suspended on the main chain.
[0051] ② Gel reaction (inorganic network formation): Silalkoxy groups hydrolyze in the presence of water / catalyst to generate silanols (Si-OH), and then the silanols condense and dehydrate to form siloxane bonds (Si-O-Si), ultimately constructing a two-dimensional or three-dimensional inorganic silicon-oxygen network.
[0052]
[0053] ③ Final material structural characteristics: Amide groups (-CONH2): hydrogen bonding sites, enhancing water solubility and strength; Imidazole rings (from VIM): coordination / ion interaction sites; Benzene rings (from DVB): hydrophobic regions, improving mechanical strength; Silicon-oxygen network (from VTMS): -[Si-O-Si-O] n -Inorganic framework.
[0054] Please refer to Figure 2 The synthesis process of the gel system of the present invention is as follows: AM, VIM, DVB, and VTMS are first added to an aqueous solution and stirred thoroughly. Then, SDS is added to ensure that the water-insoluble particles such as VIM, DVB, and VTMS are uniformly dispersed in the aqueous phase system. After stirring, a stable precursor solution system is formed. After adding KPS, the reaction is carried out at 50℃-70℃ for 9-12 hours. Under the initiation of free radicals, each functional monomer undergoes a copolymerization reaction. AM constitutes the polymer backbone, DVB and VTMS provide crosslinking sites, and VIM endows the system with a nitrogen-containing heterocyclic functional structure, ultimately forming a polyacrylamide-based gel system with a three-dimensional crosslinked network.
[0055] In some examples, the crosslinking agent mixture can be selected from any value between 0.6% and 1% by weight.
[0056] For example, the crosslinking agent mixture may contain, but is not limited to, 0.6%, 0.7%, 0.8%, 0.9%, and 1% by weight.
[0057] In some examples, the mass ratio of acrylamide to 1-vinylimidazole is (2-4):(0.07-0.2).
[0058] In some examples, the mass ratio of divinylbenzene to vinyltrimethoxysilane is (0.05-0.13):(0.05-0.07).
[0059] In some examples, the gel material was at 120°C and 20 × 10⁻⁶. 4 The swelling rate after aging in mg / L saline for 7 days was 388%-659%.
[0060] In some examples, the tensile strength of the gel material is not less than 13 kPa.
[0061] According to another aspect of the embodiments of this application, a method for preparing a novel gel material suitable for reservoir profile control is also provided, comprising the following steps:
[0062] Acrylamide and sodium dodecyl sulfate were added to deionized water and stirred until completely dissolved to obtain the first mixture.
[0063] 1-Vinylimidazole, vinyltrimethoxysilane, and divinylbenzene were added sequentially to the first mixture and stirred until homogeneous to obtain the second mixture.
[0064] Add potassium persulfate aqueous solution to the second mixture, stir and mix to obtain the reaction precursor solution;
[0065] The precursor solution was transferred to a sealed container, nitrogen gas was introduced to purge oxygen, and the container was sealed. The reaction was carried out at 50℃-70℃ for 9-12 hours to obtain the gel material.
[0066] It should be noted that the raw materials used in this invention, such as acrylamide, sodium dodecyl sulfate, 1-vinylimidazole, vinyltrimethoxysilane, divinylbenzene, and potassium persulfate, are all commercially available industrial-grade products. Their preparation or synthesis methods have been disclosed in the prior art, and the products obtained by different preparation or synthesis methods can all be applied to the technical solution of this invention. The different preparation or synthesis methods will not affect the technical effect of this invention. Those skilled in the art can refer to the prior art to select a suitable method or purchase commercially available finished products for use without any creative effort. No limitation is made here.
[0067] In some examples, the concentration of the potassium persulfate aqueous solution is 0.02 g / mL to 0.04 g / mL.
[0068] In some examples, the stirring speed is 300 rpm-500 rpm and the stirring time is 15 min-45 min.
[0069] In some examples, the time for purging oxygen with nitrogen is 30-60 minutes.
[0070] According to another aspect of the embodiments of this application, a novel gel material suitable for reservoir profile control as described in any of the first aspects is also provided, or a novel gel material suitable for reservoir profile control prepared by the preparation method described in any of the second aspects, with a formation temperature ≥120℃ and a formation water salinity ≥20×10⁻⁶. 4 Application of mg / L in reservoir profile control and water shut-off operations.
[0071] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed according to national standards. If no corresponding national standard exists, then common international standards, conventional conditions, or conditions recommended by the manufacturer are followed.
[0072] Example 1
[0073] This embodiment 1 provides a novel gel material suitable for reservoir profile control and its preparation method. The preparation method includes the following steps:
[0074] Add 3 g of acrylamide monomer and 0.15 g of sodium dodecyl sulfate surfactant to 15 mL of deionized water and stir until fully dissolved. Then, in a fume hood, add 100 μL of functional monomer 1-vinylimidazole, 70 μL of coupling agent vinyltrimethoxysilane, and 60 μL of crosslinking agent divinylbenzene. Add 0.003 g of initiator potassium persulfate. Place the beaker on a magnetic stirrer at 300 rpm and stir at a constant speed for 30 minutes to obtain a homogeneous, stable, and translucent solution. Transfer the solution to a sealed glass container and continuously purge with nitrogen gas for 30 minutes. Then, place the container in an oven at 60°C for 12 hours to gel, finally obtaining the gel material.
[0075] Example 2
[0076] Example 2 provides a novel gel material and preparation method suitable for reservoir profile control. The only difference from Example 1 is that the amount of acrylamide is 2g, the amount of divinylbenzene is 0.07g, and the amount of vinyltrimethoxysilane is 0.06g.
[0077] Example 3
[0078] Example 3 provides a novel gel material and its preparation method suitable for reservoir profile control. The only difference from Example 1 is that the amount of divinylbenzene used is 0.10 g, and the amount of vinyltrimethoxysilane used is 0.05 g. The product obtained in Example 3 is as follows: Figure 3 As shown.
[0079] Example 4
[0080] Example 4 provides a novel gel material and preparation method suitable for reservoir profile control. The only difference from Example 1 is that the amount of acrylamide is 4 g, the amount of divinylbenzene is 0.13 g, and the amount of vinyltrimethoxysilane is 0.05 g.
[0081] Comparative Example 1
[0082] Comparative Example 1 provides a polyacrylamide hydrogel, which differs from Example 1 only in that: 1-vinylimidazolium, divinylbenzene and vinyltrimethoxysilane are not added, only acrylamide is used as the monomer and N,N'-methylenebisacrylamide is used as the crosslinking agent. The remaining components and preparation steps are the same as in Example 1, in order to verify the difference in technical effect between conventional polyacrylamide hydrogel and the gel material of the present invention.
[0083] To better understand the present invention, the following performance evaluation tests were performed on the embodiments and comparative examples.
[0084] Test 1
[0085] Test 1 was a scanning electron microscope (SEM) test. The product of Example 3 was selected as the sample. The specific test procedure was as follows: The prepared block hydrogel sample was cooled with liquid nitrogen and then freeze-dried in a -60°C freeze dryer (LGJ-12A) for 48 hours until all moisture was removed. Subsequently, the dried gel sample was cut into 5×5×1 mm blocks, fixed to sample posts with conductive tape, and uniformly sputtered with gold. The gel particle suspension was diluted in pure water and dried at room temperature to prepare particle samples for SEM testing. Finally, the microstructure of the block and granular gels was observed using a scanning electron microscope at 5.0 kV.
[0086] Please refer to Figure 4 , Figure 4The image shown is a scanning electron microscope image of Example 3. It can be seen from the image that the material exhibits a typical three-dimensional porous network structure, with macropores of 40 μm and a large number of micropores of 0-10 μm. This multi-scale porous structure is a typical feature of hydrogels after internal moisture loss during the drying process, which proves that the material is a hydrogel material. It can also be seen that the pores of the material are interconnected, forming a continuous pore network, which is conducive to the rapid transport of water and exchange of substances in the swollen state of the hydrogel, and also provides a structural basis for its adsorption.
[0087] Test 2
[0088] Test 2 is an infrared spectroscopy test. The products of Examples 1-4 are selected as samples. The specific test steps are as follows: the prepared sheet-like hydrogel samples are placed in a vacuum drying oven for freeze-drying for 48 hours. The freeze-dried samples are cut into samples with a diameter of 3 mm, placed on the infrared spectrometer, and the pressure rod is rotated to apply uniform and moderate pressure to the samples to ensure that the samples and crystals form a close optical contact. The samples are then scanned.
[0089] Please refer to Figure 5 , Figure 5 The images shown are infrared (IR) test results from Examples 1-4. The results indicate that the positions of the main absorption peaks of each sample are basically the same, suggesting that their main chemical structures are similar. The sample at 3365.22 cm⁻¹... -1 The peak at 2963.62 cm⁻¹ is related to NH₃ stretching. -1 An absorption peak for the CH stretching vibration appears at 1658.99 cm⁻¹. -1 The broad peaks are related to the stretching vibrations of C=O and C=N. 1257.38 cm⁻¹ -1 The appearance of peaks is related to CN stretching vibrations. Additionally, the 1200-1000 cm⁻¹ peak... -1 A distinct Si-O-Si / Si-OC characteristic absorption band appears within this range. (797.43 cm⁻¹) -1 The characteristic peak corresponds to the out-of-plane bending vibration absorption of the benzene ring (CH). 687.50 cm⁻¹ -1 The peaks observed are related to the CN stretching vibration of the imidazole ring. Comprehensive analysis shows that amide groups, silicon-containing cross-linked structures, and aromatic ring structures are present in all samples, indicating that AM, VTMS, and DVB have been successfully introduced into the gel network. This proves that the characteristic peaks of the core functional groups of the prepared gel match the target structure, and the target gel was successfully prepared.
[0090] Test 3
[0091] Test 3 is a thermogravimetric analysis. The products of Examples 1-2 were selected as samples. The specific test steps are as follows: the prepared sheet-like hydrogel samples were placed in a vacuum drying oven for freeze-drying for 48 h. The thermogravimetric analyzer was turned on and N2 was introduced throughout the process. The heating slope was set to 10 ℃ / min and the scanning temperature range was 25-500℃. 30 mg of the sample was placed in a crucible containing alumina powder for testing.
[0092] Please refer to Figure 6 , Figure 6 The results show the thermogravimetric analysis (TGA) results for Examples 1 and 2. The results indicate that the decomposition initiation temperatures of the particles in Examples 1 and 2 are 238°C and 249°C, respectively. Example 1 experienced a weight loss of 14.89% at 238°C and a further weight loss of 68.96% at 500°C. Example 2 experienced weight losses of 13.93% and 60.44% at 249°C and 500°C, respectively. This demonstrates that the thermal decomposition initiation temperature of Example 2 is higher than that of the gel in Example 1, while its thermal weight loss is less. This is attributed to the effect of the crosslinking agent, divinylbenzene. The results show that the present invention possesses excellent thermal properties.
[0093] Test 4
[0094] Test 4 is an angular frequency scanning test. Examples 1-4 and Comparative Example 1 are selected as samples. The specific test steps are as follows: the gel sample is made into a thin sheet and placed on the rheometer test platform. The angular frequency range is set to 0.1-100 rad / s and the density is set to 10 to test the storage modulus (G') and loss modulus (G'') of the gel sample.
[0095] Please refer to Figure 7 , Figure 7 The figures show the relationship between frequency and storage modulus (G') and loss modulus (G'') of Examples 1-4 and Comparative Example 1. The results show that G' and G'' increase with increasing frequency in the angular frequency range of 0.1-100 rad / s, indicating that frequency affects G' and G''. This is due to the rapid rearrangement of the polymer network at higher frequencies. Furthermore, G' remains higher than G'' throughout the entire scanning frequency range, indicating the gel's elasticity. The curve comparison shows that Example 2 has the highest G' and G'', indicating its strongest network structure and highest crosslinking density, while Comparative Example 1, a typical polyacrylamide gel, exhibits the lowest modulus. This demonstrates that the novel material has better strength compared to typical polyacrylamide gels.
[0096] Test 5
[0097] Test 5 is a mechanical tensile test. Examples 1-4 and Comparative Example 1 were selected as samples. The specific test procedure was as follows: the gel sample was prepared into a thin sheet and then cut into strips of 30×6×2 mm. The samples were then stretched at a speed of 10 mm / min until they broke. To ensure the accuracy of the experiment, each sample was tested five times.
[0098] The test results are shown in Table 1:
[0099] Table 1. Mechanical tensile test results of each sample
[0100] As can be seen from Table 1, the strength of Examples 1, 2, 3, and 4 is higher than that of Comparative Example 1. This is because the crosslinking agent divinylbenzene and the coupling agent vinyltrimethoxysilane were added to the examples, making the internal structure of the gel more compact and the strength higher. Although the elongation is slightly lower than that of Comparative Example 1, the strain of Examples 1 and 4 can still reach more than 200%, namely 203% and 269%, respectively, which have good mechanical properties.
[0101] Test 6
[0102] This test 6 is an aging test under different conditions. Examples 1-4 and Comparative Example 1 were selected as samples. The specific test steps were as follows: time gradients were set to 7 days and 14 days; temperature gradients were set to room temperature, 110℃, and 120℃; and mineralization gradients were set to 0 and 20×10⁻⁶. 4 mg / L, and conduct cross-condition experiments.
[0103] The test results are shown in Table 2:
[0104] Table 2. Swelling rate (%) of each sample under different conditions (constant mineralization of 20 × 10⁻⁶) 4 mg / L
[0105]
[0106] Please refer to Figure 8 , Figure 8 The figures shown are from Examples 3 and 4 at 120°C and 20 × 10⁻⁶. 4Images of the materials aged for seven days under mg / L conditions, as shown in Table 2, indicate that the swelling properties of Examples 1-4 in room temperature saline solution were greater than those in room temperature clean water. This suggests that the specific salt ion effect and ionic bond recombination in the saline solution promoted network expansion, while in clean water, hydrophobic groups aggregated to form dense hydrophobic microdomains, thus limiting swelling. The performance of the examples and comparative examples under high temperature and high salt conditions demonstrates that the prepared novel material exhibits good temperature and salt resistance, and its overall structure remains intact and the swelling rate remains stable after 7 days of aging. In contrast, the comparative example readily hydrolyzes at high temperatures.
[0107] Test 7
[0108] Test 7 is a sealing performance test. Examples 1-4 and Comparative Example 1 were selected as samples. The specific test steps are as follows: Prepare 5 sand-filled pipes (1 meter long and 0.05 meters in diameter), inject Examples 1-4 and Comparative Example 1 into the sand-filled pipes respectively, record the inlet and outlet pressures, and calculate the sealing rate based on the data.
[0109] Please refer to Figure 9 , Figure 9 This illustration depicts the profile control and water shut-off process of the product of this invention in a heterogeneous reservoir. During the injection phase, gel particles enter the formation along with the injected fluid. Due to the low flow resistance in high-permeability layers and the preferential passage of the injected fluid, the gel particles selectively enter the high-permeability layers and migrate along the dominant channels. As the injection volume increases, the gel particles gradually become trapped and aggregate within the high-permeability layers, forming stable plugging zones locally, thereby increasing the flow resistance of the high-permeability channels. During the subsequent water drive process, the fluid that originally surged along the high-permeability layers is restricted by the plugging effect, and its flow direction changes, diverting and redirecting from the high-permeability layers to the low-permeability layers on both sides, thus achieving profile control and water shut-off.
[0110] The test results are shown in Table 3:
[0111] Table 3 Comparison of plugging performance of various samples
[0112]
[0113] Table 3 shows the water-driven pressure difference and plugging rate before and after plugging in Examples 1-4 and Comparative Example 1. As can be seen from Table 3, the water-driven pressure difference before plugging for each sample is within the range of 0.0032-0.0035 MPa, indicating good comparability of the baseline flow conditions. Compared with the comparative example, the water-driven pressure difference after plugging in Examples 1-4 is significantly increased, ranging from 0.0589 to 0.0712 MPa, with an average of 0.0639 MPa; approximately 5.15 times that of the comparative example; correspondingly, the plugging rate reaches 90.9-93.5%, an increase of about 30% compared to the comparative example, indicating that the hydrogel can form a more effective flow-blocking structure in porous media and significantly improve water plugging performance.
[0114] Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible subranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed subranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the range referred to.
[0115] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A novel gel material suitable for reservoir profile control, characterized in that, The gel material is formed by pre-crosslinking and hybridization reaction of 16%-17% polymer monomer mixture, 0.6%-1% crosslinking agent mixture, 0.2%-0.81% surfactant, 0.02%-0.03% initiator and the balance deionized water by weight percentage. The polymer monomer mixture includes acrylamide and 1-vinylimidazole; the crosslinking agent mixture includes divinylbenzene and vinyltrimethoxysilane; the surfactant is sodium dodecyl sulfate; and the initiator is potassium persulfate.
2. The gel material according to claim 1, characterized in that, The mass ratio of the acrylamide to the 1-vinylimidazole is (2-4):(0.07-0.2).
3. The gel material according to claim 1, characterized in that, The mass ratio of divinylbenzene to vinyltrimethoxysilane is (0.05-0.13):(0.05-0.07).
4. The gel material according to claim 1, characterized in that, The gel material is subjected to 120℃ and 20×10 4 The swelling rate after aging in mg / L saline for 7 days was 388%-659%.
5. The gel material according to claim 1, characterized in that, The tensile strength of the gel material is not less than 13 kPa.
6. A method for preparing a novel gel material suitable for reservoir profile control according to any one of claims 1-5, characterized in that, Includes the following steps: Acrylamide and sodium dodecyl sulfate were added to deionized water and stirred until completely dissolved to obtain the first mixture. 1-Vinylimidazole, vinyltrimethoxysilane and divinylbenzene were added sequentially to the first mixture and stirred until homogeneous to obtain the second mixture. Add potassium persulfate aqueous solution to the second mixture, stir and mix to obtain the reaction precursor solution; The reaction precursor solution was transferred to a sealed container, nitrogen gas was introduced to purge oxygen, and the container was sealed. The reaction was carried out at 50℃-70℃ for 9-12 hours to obtain the gel material.
7. The method according to claim 6, characterized in that, The concentration of the potassium persulfate aqueous solution is 0.02 g / mL to 0.04 g / mL.
8. The method according to claim 6, characterized in that, The stirring speed is 300rpm-500rpm, and the stirring time is 15min-45min.
9. The method according to claim 6, characterized in that, The time for purging oxygen with nitrogen is 30-60 minutes.
10. A novel gel material suitable for reservoir profile control according to any one of claims 1-5, with a formation temperature ≥120℃ and formation water salinity ≥20×10⁻⁶. 4 Application of mg / L in reservoir profile control and water shut-off operations.